Attentional Control Moderates the Relationship between Social Anxiety Symptoms and Attentional Disengagement from Threatening Information - Taylor, Charles T. (J Behav Ther Exp Psychiatry, 2015)
BACKGROUND AND OBJECTIVES: Social anxiety is characterized by biased attentional processing of social information. However, heterogeneity of extant findings suggests that it may be informative to elucidate individual difference factors that modulate the processing of emotional information. The current study examined whether individual differences in components of attentional control (AC – shifting and focusing) moderated the link between social anxiety and attentional engagement and disengagement biases for threat-relevant cues. METHODS: Seventy-five undergraduate students completed well-established measures of social anxiety symptoms, AC, and attentional bias for social threat information (modified probe detection task). RESULTS: Moderation analyses revealed that at low levels of AC-shifting, increased social anxiety was associated with slower disengagement from threat-relevant compared to neutral social cues. In contrast, at high levels of AC-shifting, social anxiety was associated with faster disengagement from threat-relevant compared to neutral stimuli. Individual differences in AC-focusing did not moderate the social anxiety-attentional bias link. LIMITATIONS: Causal inferences cannot be made given the cross-sectional study design. The sample comprised individuals displaying a range of self-reported social anxiety symptoms; thus, generalizability to clinical samples remains to be established. The measurement of AC relied on subjective participant report. CONCLUSIONS: The current findings underscore the importance of AC processes in understanding the nature of attentional bias mechanisms in anxiety.